LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN MINAT BELAJAR SISWA DENGAN TEKNIK DISKUSI KELOMPOK PADA PELAJARAN MATEMATIKA DI MTS AL MUDDAKIR BANJARMASIN - Norma Afriani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2017)
The problem of this research is Is Guidance Services Group with an effective group discussion techniques to Increase Interest in Learning students In Mathematics Lesson in Mts Al Muddakir Banjarmasin. Goals to be achieved in this research is to determine the extent of Guidance Services group by group discussion techniques effectively to improve student learning interest in math in Mts Al Muddakir Banjarmasin. The method used in conducting this research is quantitative experiments. Place of research conducted in Mts Al Muddakir Banjarmasin which is located in the village of Banua Anyar. The object of research is group counseling services to increase student interest in math. The conclusion of this research is an increase in the pre-test phase (before treatment), counseling services group with group discussion techniques, and afterwards at the stage of post-test (after treatment). And group counseling services with effective group discussion techniques to increase student interest in math in Mts Al Muddakir Banjarmasin.